Autopsy Findings and Venous Thromboembolism in Patients With COVID-19: A Prospective Cohort Study - Wichmann, Dominic (Ann Intern Med, 2020)
BACKGROUND: The new coronavirus, severe acute respiratory syndrome coronavirus-2 (SARS–CoV-2), has caused more than 210 000 deaths worldwide. However, little is known about the causes of death and the virus's pathologic features. OBJECTIVE: To validate and compare clinical findings with data from medical autopsy, virtual autopsy, and virologic tests. DESIGN: Prospective cohort study. SETTING: Autopsies performed at a single academic medical center, as mandated by the German federal state of Hamburg for patients dying with a polymerase chain reaction–confirmed diagnosis of COVID-19. PATIENTS: The first 12 consecutive COVID-19–positive deaths. MEASUREMENTS: Complete autopsy, including postmortem computed tomography and histopathologic and virologic analysis, was performed. Clinical data and medical course were evaluated. Results: Median patient age was 73 years (range, 52 to 87 years), 75% of patients were male, and death occurred in the hospital (n = 10) or outpatient sector (n = 2). Coronary heart disease and asthma or chronic obstructive pulmonary disease were the most common comorbid conditions (50% and 25%, respectively). Autopsy revealed deep venous thrombosis in 7 of 12 patients (58%) in whom venous thromboembolism was not suspected before death; pulmonary embolism was the direct cause of death in 4 patients. Postmortem computed tomography revealed reticular infiltration of the lungs with severe bilateral, dense consolidation, whereas histomorphologically diffuse alveolar damage was seen in 8 patients. In all patients, SARS–CoV-2 RNA was detected in the lung at high concentrations; viremia in 6 of 10 and 5 of 12 patients demonstrated high viral RNA titers in the liver, kidney, or heart. LIMITATION: Limited sample size. CONCLUSION: The high incidence of thromboembolic events suggests an important role of COVID-19–induced coagulopathy. Further studies are needed to investigate the molecular mechanism and overall clinical incidence of COVID-19–related death, as well as possible therapeutic interventions to reduce it. PRIMARY FUNDING SOURCE: University Medical Center Hamburg-Eppendorf.